Teaching the whole teen everyday practices that promote success and resilience in school and life - Poliner, Rachel A.; Benson, Jeffrey (Corwin, 2017)
How can you help teens thrive now and for life? Support them as whole learners. Developing independence and responsibility. Collaborating and communicating effectively. Establishing valuable work habits. Harnessing emotions and motivation. In this insightful, culturally responsive guide, Poliner and Benson integrate these lifelong skills into daily practices through: Practical applications for diverse populations in every class, advisory, team, or club; The latest research on best practices from adolescent psychology, neuroscience, school climate; Tools for teachers, administrators, counselors, and parents to help teens succeed now and later in school, home, workplace, and community. Teaching the Whole Teen supports adolescents and adults within the school to thrive. -- Provided by publisher.